Effect of Shock Loading on ω Phase Formation in Pre-Strained Pure Titanium - Masuda, Takahiro; Shiraishi, Takahisa; Tokuda, Makoto; Horita, Zenji; Hokamoto, Kazuyuki; Kiguchi, Takanori; Tanaka, Shigeru (MATERIALS TRANSACTIONS, 2025)
This study examines the effect of shock loading on allotropic transformation of pure Ti. The samples are initially processed by high-pressure torsion under 2 and 6 GPa to impart intense shear strain and they are subjected to shock loading at an impact speed of 702 m/s. X-ray diffraction analysis as well as hardness measurement is carried out to check the formation of ω phase. It is shown that intense shear strain before shock loading does not promote the ω phase formation but concurrent shear straining under high pressure is effective for the ω phase formation.